The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/jocd.12738
|View full text |Cite
|
Sign up to set email alerts
|

Antera 3D camera: A novel method for evaluating the therapeutic efficacy of fractional CO2 laser for surgical incision scars

Abstract: For scar therapeutic evaluation, Antera 3D camera is objective and accurate, and is worthy of wide promotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Traditionally, hypertrophic scarring is assessed using various scales including the Vancouver Scar Scale (VSS) or the modified patient and observer scar assessment scale (POSAS) [232]. Recent methods for scar assessment include the use of a three-dimensional camera [233]. Three-dimensional stereo-photogrammetry was recently introduced as a reliable method for assessing scar volume in clinics [234].…”
Section: Molecular Modulation Of Hypertrophic Scarring Following Severe Burnsmentioning
confidence: 99%
“…Traditionally, hypertrophic scarring is assessed using various scales including the Vancouver Scar Scale (VSS) or the modified patient and observer scar assessment scale (POSAS) [232]. Recent methods for scar assessment include the use of a three-dimensional camera [233]. Three-dimensional stereo-photogrammetry was recently introduced as a reliable method for assessing scar volume in clinics [234].…”
Section: Molecular Modulation Of Hypertrophic Scarring Following Severe Burnsmentioning
confidence: 99%
“…Our previous study compared the traditional evaluation methods with Antera3D score and recommended the further application of Antera3D score, which reflected the therapeutic efficacy in four aspects, namely color, texture, melanin, and hemoglobin. 12 However, in clinical practice, systemic evaluation is conducted based on the combined application of VSS, UNC4P, and Antera3D score, rather than the summation of these scores. The purpose of applying these three evaluation methods in combination is to make up for the deficiency of each individual score and to better guide the clinical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Age (y) 28. of Antera3D score, which reflected the therapeutic efficacy in four aspects, namely color, texture, melanin, and hemoglobin. 12 In a retrospective clinical review, the postinflammatory hyperpigmentation is observed in 51% cases. 13 In addition, it is demonstrated that superficial fractional CO 2 laser therapy causes more epithelial damage, thus resulting in an increased risk of hyperpigmentation.…”
Section: Demographic Characteristics N = 79mentioning
confidence: 99%
“…We also objectively assessed the patients' scar height, pigmentation, and vascularity using a three‐dimensional skin imaging device (Antera 3D™; Miravex Limited) that quantified these characteristics for an accurate comparison of the before and after images with little error. This device has been widely used in studies of various skin disorders 19–22 …”
Section: Methodsmentioning
confidence: 99%